2008
DOI: 10.1161/circep.108.803650
|View full text |Cite
|
Sign up to set email alerts
|

Novel Contact Force Sensor Incorporated in Irrigated Radiofrequency Ablation Catheter Predicts Lesion Size and Incidence of Steam Pop and Thrombus

Abstract: Background— An open-irrigated radiofrequency (RF) ablation catheter was developed to measure contact force (CF). Three optical fibers measure microdeformation of the catheter tip. The purpose of this study was to (1) validate the accuracy of CF sensor (CFS) (bench test); and (2) determine the relationship between CF and tissue temperatures, lesion size, steam pop, and thrombus during RF ablation using a canine thigh muscle preparation. Methods and Results— CFS measurements (total 1409) from 2 catheters in 3 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
519
5
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 573 publications
(556 citation statements)
references
References 26 publications
(38 reference statements)
15
519
5
1
Order By: Relevance
“…Experimental data obtained with objective contact assessment technologies indicate a correlation between contact and lesion size. 18 The improved outcome observed in our study may therefore be in part interpreted as the clinical result of improved lesion formation and lesion maintenance. Other factors contributing to clinical outcome are likely to be related to the stability of the catheter position over longer ablation periods and the ability to reliably access different ablation target sites.…”
Section: Impact Of Steerable Sheath Access On Clinical Outcomementioning
confidence: 59%
“…Experimental data obtained with objective contact assessment technologies indicate a correlation between contact and lesion size. 18 The improved outcome observed in our study may therefore be in part interpreted as the clinical result of improved lesion formation and lesion maintenance. Other factors contributing to clinical outcome are likely to be related to the stability of the catheter position over longer ablation periods and the ability to reliably access different ablation target sites.…”
Section: Impact Of Steerable Sheath Access On Clinical Outcomementioning
confidence: 59%
“…They make use of several sensing principles, such as strain-gauges [8], piezoresistivity [9], PVDF films [1] and fibre-optic technology [10], [11], [15]. However, only a small number of sensors were developed for the detection of contact forces between the catheter and tissue [12], [13].…”
Section: Force Feedback In Cardiac Catheterizationmentioning
confidence: 99%
“…The difficulty of directly assessing the degree and quality of contact between the catheter tip and the target tissue has been demonstrated even in experienced operators 2. Moreover, preclinical research has shown that insufficient CF can result in ineffective lesion formation 5, 6, 7. Therefore, poorer clinical outcome can occur even if tactile feedback, fluoroscopy, and high‐amplitude electrograms appear to indicate good contact 2.…”
Section: Discussionmentioning
confidence: 99%